Preference for Combinations of Hearing Aid Signal Processing. - Rallapalli, Varsha; Schauer, Jacob; Souzaa, Pamela (Journal of Speech, Language & Hearing Research, 2022)
Purpose: The purpose of this study was to determine how multiple types of signal processing activated together influence listeners' preferences. Method: Participants were adults with mild to moderately severe sensorineural hearing loss. Stimuli were spatialized low-context sentences mixed with sixtalker babble at 3 and 8 dB signal-to-noise ratios (SNRs). Stimuli were processed with three common hearing aid processing algorithms: wide dynamic range compression (WDRC), frequency compression (FC), and digital noise reduction (DNR). A full-factorial design with two levels for each algorithm (WDRC & DNR: mild versus strong; FC: ON versus OFF; clinically relevant ranges) was evaluated. Preference was measured using a paired-comparison task within a choice-based conjoint analysis framework. Remote data collection methods were used. A signal fidelity metric quantified the acoustic effects across conditions. Results: At 3 dB SNR, participants preferred a combination of Slow WDRC and Mild DNR, although the mean preference was small (odds ratio close to 1). At both SNRs when Strong DNR was used, Fast WDRC was preferred over Slow WDRC. This may be related to signal fidelity, which was lower for the combination of Fast WDRC and Mild DNR and higher for the combination of Slow WDRC and either Mild DNR or Strong DNR. There was no effect of FC on preference or signal fidelity. Conclusions: WDRC and DNR together influenced both listeners' preferences and signal fidelity in the investigated listening conditions. On average, the small effect sizes suggest that minor fine-tuning adjustments to hearing aid algorithms may not result in a substantial change in clinical outcomes.